Emerging investigator series: entrapment of uranium–phosphorus nanocrystals inside root cells of Tamarix plants from a mine waste site. Issue 1 (16th December 2020) - Rodriguez-Freire, Lucia; DeVore, Cherie L.; El Hayek, Eliane; Berti, Debora; Ali, Abdul-Mehdi S.; Lezama Pacheco, Juan S.; Blake, Johanna M.; Spilde, Michael N.; Brearley, Adrian J.; Artyushkova, Kateryna; Cerrato, José M.
Abstract : Uranium uptake and accumulation in the roots of Tamarix plants, leading to extracellular U precipitation, and the intracellular entrapment of U–P nanocrystals. Abstract : We investigated the mechanisms of uranium (U) uptake by Tamarix (salt cedars) growing along the Rio Paguate, which flows throughout the Jackpile mine near Pueblo de Laguna, New Mexico. Tamarix were selected for this study due to the detection of U in the roots and shoots of field collected plants (0.6–58.9 mg kg −1 ), presenting an average bioconcentration factor greater than 1. Synchrotron-based micro X-ray fluorescence analyses of plant roots collected from the field indicate that the accumulation of U occurs in the cortex of the root. The mechanisms for U accumulation in the roots of Tamarix were further investigated in controlled-laboratory experiments where living roots of field plants were macerated for 24 h or 2 weeks in a solution containing 100 μM U. The U concentration in the solution decreased 36–59% after 24 h, and 49–65% in two weeks. Microscopic and spectroscopic analyses detected U precipitation in the root cell walls near the xylems of the roots, confirming the initial results from the field samples. High-resolution TEM was used to study the U fate inside the root cells, and needle-like U–P nanocrystals, with diameter <7 nm, were found entrapped inside vacuoles in cells. EXAFS shell-by-shell fitting suggest that U is associated with carbon functional groups. The preferable binding of U to the root cell walls may explain the U retention in the roots of Tamarix, followed by U–P crystal precipitation, and pinocytotic active transport and cellular entrapment. This process resulted in a limited translocation of U to the shoots in Tamarix plants. This study contributes to better understanding of the physicochemical mechanisms affecting the U uptake and accumulation by plants growing near contaminated sites.